2020
DOI: 10.3390/cli9010005
|View full text |Cite
|
Sign up to set email alerts
|

The Agro-Meteorological Caused Famines as an Evolutionary Factor in the Formation of Civilisation and History: Representative Cases in Europe

Abstract: Throughout history, food adequacy has been one of the most critical parameters for the survival of human societies. The prevailing atmospheric conditions have always been recognised as the primary and most uncontrolled factors that determine crop production, both quantitatively and qualitatively. However, this is only a part of the effects chain. In order to assess the magnitude of the potential cultural impacts of weather changes in a region, it is crucial to comprehend the underlying mechanism of successive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…Given the expected major shifts in food security owing to CC, the upcoming nutrition certainty will rely on agricultural systems that are resilient to production failure when faced with crucial short-run threats [101,102]. The impacts of weather and seasonal climate extremes (drought, temperature extremes, flooding, major rainfalls and cyclones) on food consumption are widely reported, given that food security is strained in the extreme events' immediate aftermath [9,[103][104][105][106][107][108]. In the concept of securing global nutrition, the association between food security and climate risk indicates that the latter's management must be incorporated into future sustainable development goals (e.g., SDG2: "end hunger, achieve food security and improved nutrition and promote sustainable agriculture").…”
Section: Agriculture and Food Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…Given the expected major shifts in food security owing to CC, the upcoming nutrition certainty will rely on agricultural systems that are resilient to production failure when faced with crucial short-run threats [101,102]. The impacts of weather and seasonal climate extremes (drought, temperature extremes, flooding, major rainfalls and cyclones) on food consumption are widely reported, given that food security is strained in the extreme events' immediate aftermath [9,[103][104][105][106][107][108]. In the concept of securing global nutrition, the association between food security and climate risk indicates that the latter's management must be incorporated into future sustainable development goals (e.g., SDG2: "end hunger, achieve food security and improved nutrition and promote sustainable agriculture").…”
Section: Agriculture and Food Securitymentioning
confidence: 99%
“…Numerous complexities characterize the agricultural sector, and the end user/farmer lacks familiarity with new technologies [7,8]. In addition, agriculture constitutes a fundamental sector of human survival and the global economy since foodstuffs directly or indirectly originate from crop and animal production [9][10][11]. This publication attempts to provide brief answers to simple questions about climate services, specifically to those linked to the agricultural sector, such as farmers, agronomists, agriculture-related institutes, and private companies.…”
Section: Introductionmentioning
confidence: 99%
“…As known, the agricultural sector is crucially dependent on environmental, climate and weather conditions and the relationships between both food production and quality and climate factors are among the main objects and concerns in the studies on climate change (Bezner Kerr et al 2022;Anderson et al 2023;Bozzola et al 2018;Ben Mhenni et al 2021;Wang et al 2017). At a global level, crops' productions already show effects in yields, quality and distributions of pests and diseases, due to increasing temperatures, changing precipitation patterns and greater frequency of some extreme events, also leading to wide food safety issues and famine (Mbow et al 2019;Charalampopoulos and Droulia 2021). The shift from the past risk (linked to a known probability distribution) to uncertainty of meteorological disasters directly influences farmers' management, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they also revealed that weather impacts per-capita GDP growth through all its factors of production, with the largest impacts being on total factor productivity. Beyond the connection between weather and the above sectors, human civilization evolution is also impacted by short-term adverse weather conditions [5,8]. The Intergovernmental Panel on Climate Change (IPCC)'s framework recommendations highlight that governments, nongovernmental organizations (NGOs), and stakeholders must take appropriate actions to reduce greenhouse gas emissions in order to minimize their effects in response to global warming.…”
Section: Introductionmentioning
confidence: 99%